Landslide Suceptibility Zonation in South Sulawesi - Nasiah Nasiah; Ichsan Invanni (Forum Geografi, 2013)
Landslide Hazard Zonationin South Sulawesi. Landslides are natural disasters that can cause substantial loss in the form of life and properties. Therefore, it is necessary to inventory landslide-vulnerable areas. A weighted summation model (Dibyosaputro, 1998) was applied to determine the landslide-vulnerable areas in the Geographic Information Systems (GIS). Factors that trigger the landslides are geology (rock properties, stratigraphy, structural geology, weathering level and earthquake), climate (rainfall), soil (solum thickness), topography (slope), vegetation (vegetation density) and human (land use); Siagian Sugalan (in Sutikno, 1991) in combination with Dibyosaputro (1998). There are five classes of landslide vulnerability i.e. invulnerable, fairly vulnerable, quite vulnerable, vulnerable, and very vulnerable. In general, South Sulawesi is quite vulnerable to landslides, but there are three regencies very vulnerable for landslides; Luwu, Northern Luwu and Northern Toraja.Keyword : landslide, South Sulawesi.